Development of arduino controlled robotic arm - Norfarida Binti Awang (Education and Social Sciences Review, 2020)
Robots are playing a vital role in today’s industrial automation and monitoring system. As technology developed, these robots have increased their applications. Working robots that cooperate to the people makes the work less effort and uncomplicated. A robotic arm is a type of mechanical arm, usually programmable, with similar functions to a human arm. In this project, a programmable robotic arm is redesigned and implemented, and aimed to move using remote control and hand gesture from a certain distance by using wireless component. This robotic arm is based on android application control for remote operation. Inputs are sent to control the movement of the robot either to move in x-axis, y-axis or z-axis using 1Sheeld application on android smartphone. Five motors are interfaced to the microcontroller whereas one motor is used for gripper movement, while the other four motors are used at the joints of the robotic arm for movement. The android application device transmitter acts as a remote control by using hand gesture that has an advantage of adequate range, while receiver (1Sheeld) and Bluetooth device are fed to the microcontroller (Arduino) to drive DC motor via motor driver IC L298N for clockwise and anti-clockwise rotation. Remote operation is achieved by any smartphone with android upon Graphical User Interface (GUI) based touch screen operation.